Asset price bubbles and counter-cyclical monetary policy: Why central banks have been wrong and what should be done - Thomas I. Palley (Intervention. European Journal of Economics and Economic Policies, 2010)
Central banks have generally opposed targeting asset and credit market excess. This paper argues against that position. Bubbles can impose significant harm through the debt footprint effects they leave behind, and through distortions resulting from using interest rates to mitigate their aggregate demand impacts. Conventional interest rate policy is not well suited to managing bubbles, and the paper argues for adoption of a new system of asset based reserve requirements (ABRR). Not only can ABRR target asset market excess, they also strengthen counter-cyclical monetary policy.
Keywords: E52; E58; E60; 330; asset price bubbles; asset based reserve requirements